MICROSURGICAL VARICOCELECTOMY IN PRE-PUBERTAL CHILDREN: SAFETY, EFFICACY, AND REPRODUCTIVE IMPLICATIONS - A CASE REPORT AND LITERATURE REVIEW - Bakri, Syarif; Azis, Abdul; Zainal, Ahmad Taufik Fadillah; Rahmat A., Saidah; Makkaraka, Moh Anfasa Giffari (Indonesian Urological Association, 2025)
Objective: In this report, we aim to present a case of a prepubertal child with left varicocele who underwent successful microsurgical ligation. Case(s) Presentation: A 9-year-old boy was admitted to urology clinic due to his parents complaint about a mass in his left scrotum. We diagnosed this patient with grade III varicocele (Dubin-Amelar classification). The patient underwent microsurgical ligation surgery. After surgery, the mass such as